Recent Сladocera (Branchiopoda, Crustacea) in the taphocenoses of lakes in the Pechora River delta (Russia) - N.M. Nigmatullin; G.R. Nigamatzyanova; E.A. Valieva; L.A. Frolova (Учёные записки Казанского университета: Серия Естественные науки, 2021)
This paper presents the results of the hydrochemical, hydrobiological, and paleolimnological studies of 17 Arctic lakes in the Pechora River delta. Water samples and surface sediments were collected during the 2020 summer expedition to the Nenets State Nature Reserve. Based on the chemical composition of their waters, the studied lakes belong to the chloride class, sodium group II. Overall, they are characterized by shallow depths typical of this region, low mineralization (below 200 mg/L) and water hardness, as well as high dissolved oxygen levels. To assess the ecological status of the lakes, cladocerans and their subfossil remains, which have been widely recognized as reliable indicators for tracking long‐term changes in the development of freshwater ecosystems, were analyzed. A total of 23 cladoceran taxa were identified. The dominant species were Bosmina longispina (Leydig, 1860) and Chydorus cf. sphaericus (Müller, 1776) – either of these species, often displacing each other, prevailed in the lakes. Other cladoceran species were low-abundant and found sporadically: Sida crystallina (Müller, 1776), Pleuroxus uncinatus (Baird, 1850), Coronatella rectangula (Sars, 1862), and Bythotrephes longimanus (Leydig, 1860). The study also reports the first finding of Rhynchotalona latens (Sarmaja-Korjonen, Hakojarvi and Korhola, 2000), a rare glacial relict species with a narrow distribution range, in this region of Russia. The zoogeographical analysis of the data obtained on the identified taxa showed that species typical of the Palearctic and Holarctic zones prevail in the cladoceran communities under study.